Pengaruh Corporate Governance, Leverage, Size, Dan Profitabilitas Terhadap Pengungkapan Corporate Social Responsibility (CSR) Dalam Laporan Tahunan(Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2013-2015) - Timur, Risma Melati; , Eny Kusumawati, SE., MM., AK, CA (2017)
The aim of this research is to analyze the influence of corporate governance, leverage, size, and profitability on the corporate sosial responsibility in the annual report of manufacturing listed in Indonesia Stock Exchange 2013-2015. Corporate governance involved are institusional ownership and commitee audit. The measurement of corporate sosial responsibility based on the global reporting intiatives discloseru index (GRI) 2013 as seen from the company's annual report. The population of this research is manufacture companies listed in Indonesia Stock Exchange IDX) 2013-2015. Research sampling used purposive sampling technique and found 46 companies, with 3 years of observation. So, the total sample studied was 138. The collected data was analyzed using classic assumption test and then do hypothesis test. Testing the hypotesis in this study using multiple regression analysis with t-test, F, and the coefficient of determination. The results indicate that size have a significant influence on the corporate sosial responsibility (CSR). Meanwhile, institusional ownership, commitee audit, leverage, and profitability don't have significant influence on the corporate sosial responsibility (CSR).